First record of Chantransia macrospora Wood, 1887 (Batrachospermales, Rhodophyta) in semi-arid northeastern Brazil - Janiele França Vasconcelos (Biotemas, 2014)
This study presents the first record of Chantransia macrospora in the state of Rio Grande do Norte, in the semi-arid region of northeastern Brazil. Analyses of periphytic algae revealed C. macrospora individuals associated in particular with shells of Melanoides tuberculatus, a non-native species, suggesting that C. macrospora have been introduced into systems associated with the gastropods. In this context, new records of C. macrospora are still expected for the Brazilian semi-arid region in the next years.